2010
DOI: 10.1073/pnas.1001921107
|View full text |Cite
|
Sign up to set email alerts
|

The boundary between the Indian and Asian tectonic plates below Tibet

Abstract: The fate of the colliding Indian and Asian tectonic plates below the Tibetan high plateau may be visualized by, in addition to seismic tomography, mapping the deep seismic discontinuities, like the crust-mantle boundary (Moho), the lithosphere-asthenosphere boundary (LAB), or the discontinuities at 410 and 660 km depth. We herein present observations of seismic discontinuities with the P and S receiver function techniques beneath central and western Tibet along two new profiles and discuss the results in conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
355
2
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 372 publications
(415 citation statements)
references
References 37 publications
40
355
2
5
Order By: Relevance
“…A large number of speculative hypotheses on the Tibetan evolution have been proposed, e.g., crustal shortening and thickening (England and Houseman, 1986), eastward strike-slip extrusions of SE Asia (Li et al, 2013;Tapponnier et al, 2001Tapponnier et al, , 1982, underthrust of the Indian lithosphere beneath Asia (Li et al, 2011;Haines et al, 2003;DeCelles et al, 2002;Chemenda et al, 2000;Owens and Zandt, 1997;Powell, 1986;Klootwijk et al, 1985), destabilization and collapse of the tectonically thickened lithospheric root (Chung et al., 2009, 2005Platt and England, 1994;Houseman et al, 1981), northward crustal injection model (Chemenda et al, 2000;Zhao and Morgan, 1985), and southward subduction of the Asian lithosphere beneath Tibet (Paul et al, 2001;Roger et al, 2000;Willett and Beaumont, 1994). Recent geological, geophysical and geochemical studies suggest that the Tibetan Plateau possesses lateral variations of the subduction-related mantle structure (e.g., Chen Y et al, 2015;Chen L et al, 2013;Liang et al, 2012;Searle et al, 2011;Zhao W et al, 2011;Zhao J et al, 2010;Li et al, 2008;Yang et al, 2015) and temporal-spatial variations in post-collisional magmatism(e.g., Wang R et al, 2015;Zhang et al, 2014;Zhu et al, 2013;Chung et al, 2005Chung et al, , 2003Ding et al, 2003), which indicate that the Tibetan Plateau might have been deformed through complex tectonic events.…”
Section: Thermal and Topography Evolution On The India-asia Early Colmentioning
confidence: 99%
“…A large number of speculative hypotheses on the Tibetan evolution have been proposed, e.g., crustal shortening and thickening (England and Houseman, 1986), eastward strike-slip extrusions of SE Asia (Li et al, 2013;Tapponnier et al, 2001Tapponnier et al, , 1982, underthrust of the Indian lithosphere beneath Asia (Li et al, 2011;Haines et al, 2003;DeCelles et al, 2002;Chemenda et al, 2000;Owens and Zandt, 1997;Powell, 1986;Klootwijk et al, 1985), destabilization and collapse of the tectonically thickened lithospheric root (Chung et al., 2009, 2005Platt and England, 1994;Houseman et al, 1981), northward crustal injection model (Chemenda et al, 2000;Zhao and Morgan, 1985), and southward subduction of the Asian lithosphere beneath Tibet (Paul et al, 2001;Roger et al, 2000;Willett and Beaumont, 1994). Recent geological, geophysical and geochemical studies suggest that the Tibetan Plateau possesses lateral variations of the subduction-related mantle structure (e.g., Chen Y et al, 2015;Chen L et al, 2013;Liang et al, 2012;Searle et al, 2011;Zhao W et al, 2011;Zhao J et al, 2010;Li et al, 2008;Yang et al, 2015) and temporal-spatial variations in post-collisional magmatism(e.g., Wang R et al, 2015;Zhang et al, 2014;Zhu et al, 2013;Chung et al, 2005Chung et al, , 2003Ding et al, 2003), which indicate that the Tibetan Plateau might have been deformed through complex tectonic events.…”
Section: Thermal and Topography Evolution On The India-asia Early Colmentioning
confidence: 99%
“…4). A third conspicuous body imaged horizontally below Tibet over a distance of approximately 500 km from the Himalayan front represents Indian continental lithosphere that has underthrust Asia since the last phase of slab break-off (39,41). Taking Asian shortening (14) into account, this horizontal body represents the last 10-15 Ma of India-Asia convergence.…”
Section: Subduction History and Mantle Tomographymentioning
confidence: 99%
“…The crustal positive amplitude arrivals, seen at a depth of 40-55 km, probably imply the presence of partial eclogitic layers as well. Previous studies have shown that the Indian subduction lithosphere has thrusted northward and reached toward the BNS in the central Tibetan plateau Zhao et al, 2010;Zhao et al, 2011). Therefore, the eclogitic layer north of the BNS probably formed due to the collision of the Qiangtang and Lhasa terranes in the Middle-Late Jurassic.…”
Section: Crustal Structure Of the Central Tibetan Plateaumentioning
confidence: 99%
“…The fundamental structures that compose the lithosphere under the extreme topography of the Tibetan plateau have been gradually discovered over time, allowing us to work towards deciphering the geodynamic mechanisms that have led to the growth of the plateau. The subducting Indian lithosphere is northward-thrusting under the Tibetan plateau at an increasingly shallow angle, and reaches progressively further toward the Jinsha suture in western Tibet, the Bangong-Nujiang suture in the center, and the middle of the Lhasa terrane in the east, which has been resolved using receiver function and travel-time tomography studies (Li et al, 2008;Kind and Yuan, 2010;Zhao et al, 2010;Zhao et al, 2011). In the Himalaya and the central Tibet, doublet crustal structures are presented (Kind et al, 2002;Schulte-Pelkum et al, 2005;Nábělek et al, 2009;Wittlinger et al, 2009), which partially explains approximately 2 000 km of post-collision convergence between India and Eurasia (Molnar and Tapponnier, 1975;Patriat and Achache, 1984;Besse and Courtillot, 1988;Patzelt et al, 1996;Yi et al, 2011).…”
mentioning
confidence: 99%